Pengaruh Suhu dan Interval Waktu Penyimpanan Sampel Serum pada Pengukuran Kadar Glukosa Darah - Onne Degita Santi; Linda Rosita; Yeny Dyah Cahyaningrum (Faculty of Medicine, Universitas Islam Indonesia, 2011)
The number of samples should be checked often can not be done immediately examination due to the limited number of laboratory personnel. This phenomenon is common in clinical laboratories and private land. This needs attention given the many factors that can affect test results. Pre-analytical factors that need to be considered is the examination time interval and sample storage temperature prior to examination. Examination of blood glucose is one of the frequent checks at the hospital. The method often used is glucose oxidase method with the serum as a sample. The purpose of this research is todetermine how far the impact of delays in the inquest and the influence of storage temperature on serum blood glucose levels. The study was conducted on 30 people consisting of patients and hospital employees who are willing. Criteria for inclusion were men or women aged 20 - 40 years old and willing to follow the research. Exclusion criteria were suffering from diabetes, severe kidney disease, or are pregnant. Each subject and blood samples taken as soon as possible done on a blood sample centrifugation to obtain serum. Serum from each sample was divided into 3 tubes, which will be examined: immediate and delayed 4 hours and each tube is stored at a temperature of 2-8 °C and 25-28°C. The parameters examined were the blood chemistry of blood glucose. Examination of blood glucose using glucose oxidase method. Sampling is performed by the method of consecutive (consecutive sample). Statistical analysis by independent samples t-test. The examination of serum samples from 30 patients and hospital employees who meet the criteria of inclusion and exclusion. Comparison of results of blood glucose levels at examination time delay between 0 hours and 4 hours to get results that are not significant (p>0.05). And blood glucose levels between groups of temperature 25-28 °C and 2-8 °C no significant difference in outcome (p>0.05). The interval 0 hour storage time and 4 hours at a temperature of 25- 28 °C (room temperature) and 2-8 °C (refrigerator temperature) does not affect the results of bloodglucose levels in serum samples.